Penerapan Metode Diskusi Plus Tutor Sebaya untuk Meningkatkan Keaktifan dan Hasil Belajar Mahasiswa pada Mata Kuliah Ulumul Qur'an di Prodi PAI FTK UIN Ar-Raniry - Safrina Ariani; Aisyah Idris; Nurbayani Ali (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2022)
In implementing the group discussion method in lectures where students in groups present their assignments/papers in front of the class, were found several weaknesses such as not all student members of the presenting group mastered the material that was their assignment, only a few students were actively involved in the discussion. Furthermore, the material is not thoroughly by all the members, all of which have an impact on student learning outcomes. One way that lecturers can use to overcome the above problems is to apply the discussion method plus peer tutors. The choice of this method is expected to increase student responsibility in completing assignments and increase their activeness in the lecture process so as to improve student learning outcomes. This study aims to determine the increase in the activity and learning outcomes of unit 3 students Batch 2022/2023 PAI Department of FTK UIN Ar-Raniry through the application of the discussion method plus peer tutors in the Ulumul Qur'an Course. The subjects of this study were 35 students from unit – 03 PAI study program who are in the Ulumul Qur'an class that teach by the researcher. This research is a reflective Classroom Action Research, conducted in 3 cycles. The techniques used to collect data are test, observation and documentation techniques. Based on the analysis of the data obtained, it can be concluded that applying the discussion method plus peer tutors in the Ulumul Qur'an Course can increase learning activities of the students in discussing and working together and can improve student learning outcomes.